AC Machine Systems Mathematical Model and Parameters, Analysis, and System Performance - Gao, Jingde; Zhang, Linzheng; Wang, Xiangheng (Springer Berlin Heidelberg : Imprint: Springer, 2009)
"AC Machine Systems" stresses both analysis methods and operating performances of AC machine systems, including variable speed drive system of AC machines with power electronics and control devices, power energy system composed of AC machines and power lines, special machine system with special machines and special loads, electric machine system consisting of AC machines and excitation devices. Based on a single coil, the Multi-Loop Theory is thoroughly described, and examples of how to use the new approach are presented. This book provides a new way for analyzing the AC machine systems. This book is designed for the researchers and postgraduates in the field of electric machines and control. It's also a reference book for related technicians. This book is written in memory of Professor Jingde Gao, past-president of Tsinghua University, Member of Chinese Academy of Sciences. Another two authors, Linzheng Zhang and Xiangheng Wang both are Professors in Electrical Engineering Dept. of Tsinghua University.